Islamic Republic of Afghanistan : Interim Poverty Reduction Strategy Paper; Summary Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This Summary Report describes Afghanistan's Interim National Development Strategy (I-ANDS). It assesses the overall policy objectives, analyzes the context of and constraints to the achievement of those objectives, summarizes the government's key strategies and programs, and also reviews specific steps toward the implementation of the I-ANDS and the development of the full ANDS. It summarizes the government's proposed and ongoing sectoral programs and annual indicators against which progress may be measured. It also reviews the strategic plans developed by government line ministries and commissions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet